The Benefits and Challenges of E-procurement Implementation: A Case Study of Malaysian Company - Nawi, Mohd Nasrun Mohd; Roslan, Saniah; Salleh, Nurul Azita; Zulhumadi, Faisal; Harun, Aizul Nahar (International Journal of Economics and Financial Issues, 2016)
Traditionally, procurement covers the sales and purchase activities between two entities, which covers various aspects from searching, sourcing, negotiating, ordering, and receipt, to post-purchase review. In line with the advancement of Information and Communication Technologies, as well as with the rapid growth of the Internet, more and more people and organisations are becoming connected. In order to move with the times, many governments around the world have looked into implementing e-government systems, part of which is the e-procurement system. This paper presents the advantages as well as challenges faced when implementing an e-procurement system based on results of a case study, from the perspective of a Malaysian company (Telekom Research and Development Sdn. Bhd.) implementing an e-procurement system that has been developed internally, rather than installing an off-the-shelf software application. Internally developed e-procurement systems covers four important dimensions, namely information collected, type of application, contract negotiation, and intelligence analysis, all of which are analysed in view of e-procurement performance. The outcome of this research yielded pertinent information for the company in identifying the strengths and weaknesses of the internally developed e-procurement system, as well as enabling the organisation to highlight the practices and performance as a benchmark to measure the level of success of their own e-procurement system. Thus, due to the potential cost savings and highlighted benefits in this paper, e-procurement requires more attention from the government as related entities for greater expansion and adoption in order to ultimately contribute to the growth and well-being of the country’s economy. Keywords: Procurement, E-Procurement, Case Study, E-Government, Malaysian Industry, Internally Developed Software JEL Classifications: F23, M10